2017
DOI: 10.1080/15548627.2016.1261319
|View full text |Cite
|
Sign up to set email alerts
|

FYCO1 and autophagy control the integrity of the haploid male germ cell-specific RNP granules

Abstract: Ribonucleoprotein (RNP) granules play a major role in compartmentalizing cytoplasmic RNA regulation. Haploid round spermatids that have exceptionally diverse transcriptomes are characterized by a unique germ cell-specific RNP granule, the chromatoid body (CB). The CB shares many characteristics with somatic RNP granules but also has germline-specific features. The CB appears to be a central structure in PIWI-interacting RNA (piRNA)-targeted RNA regulation. Here, we identified a novel CB component, FYCO1, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…Autophagy could, for example, be involved in the assembly and clearance of the CB material in an analogous way that has been demonstrated for stress granules that are stress-responsive somatic RNP granules (Buchan et al 2013, Ryu et al 2014, Seguin et al 2014. Interestingly, a CB component FYCO1 (FYVE and coiled-coil domain-containing protein 1) was shown to be responsible for the recruitment of autophagosomes and lysosomes onto the CB (Da Ros et al 2017). FYCO1 binds phosphatidylinositol 3-phosphate (PtdIns3P) and MAP1LC3B/LC3B (microtubule-associated proteins 1A/1B light chain 3B) that is anchored on the autophagosomal membrane (Pankiv et al 2010.…”
Section: Interplay Of the Chromatoid Body With Other Cellular Compartmentioning
confidence: 99%
See 3 more Smart Citations
“…Autophagy could, for example, be involved in the assembly and clearance of the CB material in an analogous way that has been demonstrated for stress granules that are stress-responsive somatic RNP granules (Buchan et al 2013, Ryu et al 2014, Seguin et al 2014. Interestingly, a CB component FYCO1 (FYVE and coiled-coil domain-containing protein 1) was shown to be responsible for the recruitment of autophagosomes and lysosomes onto the CB (Da Ros et al 2017). FYCO1 binds phosphatidylinositol 3-phosphate (PtdIns3P) and MAP1LC3B/LC3B (microtubule-associated proteins 1A/1B light chain 3B) that is anchored on the autophagosomal membrane (Pankiv et al 2010.…”
Section: Interplay Of the Chromatoid Body With Other Cellular Compartmentioning
confidence: 99%
“…A doublemembrane structure, the autophagosome, forms to sequester a part of the cytosol that subsequently fuses with a lysosome. The vesicles associated with the CB contain autophagosomal and lysosomal markers, and the induction of autophagy leads to the dramatic increase in the accumulation of lysosomes onto the CB (Da Ros et al 2017). Therefore, autophagy seems to provide additional catabolic activity for the CB-dependent processes.…”
Section: Interplay Of the Chromatoid Body With Other Cellular Compartmentioning
confidence: 99%
See 2 more Smart Citations
“…The accessary material from the CB is finally discarded together with the rest of the cytoplasm in the residual body. It is demonstrated that the clearance of these materials is mainly undertook by autophagy via an FYCO1-dependent pathway, and the induction of autophagy enables the homeostasis of CB [34]. Mechanistically, FYCO1 functions as a docking site for LC3 and LAMP1-positive membranes mediating the recruitment of autophagosome and lysosome to the CB.…”
Section: The Role Of Autophagy and Spermatid Differentiationmentioning
confidence: 99%